Electronic Cigarette Use and Smoking Abstinence in Japan: A Cross-Sectional Study of Quitting Methods - Tomoyasu Hirano (International Journal of Environmental Research and Public Health, 2017)
The benefit of electronic cigarettes (e-cigarettes) in smoking cessation remains controversial. Recently, e-cigarettes have been gaining popularity in Japan, without evidence of efficacy on quitting cigarettes. We conducted an online survey to collect information on tobacco use, difficulties in smoking cessation, socio-demographic factors, and health-related factors in Japan. Among the total participants (n = 9055), 798 eligible persons aged 20–69 years who smoked within the previous five years were analyzed to assess the relationship between the outcome of smoking cessation and quitting methods used, including e-cigarettes, smoking cessation therapy, and unassisted. E-cigarette use was negatively associated with smoking cessation (odds ratio (OR) = 0.632; 95% confidence interval (CI) = 0.414–0.964) after adjusting for gender, age, health-related factors, and other quitting methods. Conversely, smoking cessation therapy (i.e., varenicline) was significantly associated with smoking cessation (OR = 1.885; 95% CI = 1.018–3.492) in the same model. For effective smoking cessation, e-cigarette use appears to have low efficacy among smokers in Japan. Allowing for the fact that this study is limited by its cross-sectional design, follow-up studies are needed to assess the prospective association between e-cigarette use and smoking cessation.